Faktor-Faktor Yang Mempengaruhi Biaya Pemeliharaan Gedung: (Studi Kasus Gedung Trihamas Finance Jakarta) - April Priyo Handoko; Socio Jiwapatria (Journal of Cross Knowledge, 2023)
The need for office space is the initiator, PT Trihamas Finance which is engaged in the car funding business, to build office buildings and facilities. The location of the building built is on Jalan TB. Simatupang kav.11 Tanjung Barat Village, Jagakarsa District, South Jakarta. The construction of this building was established in an effort to support the provision of office facilities in the South Jakarta area, especially in Tanjung Barat District. Regular building maintenance is one of the requirements that must be met, especially for office buildings that are rented. With planned maintenance and maintenance will affect the life of the plan and reduce the cost budget to a minimum. Managers incur maintenance costs through processes that have been set by management so that sometimes long waits due to procedures and time constraints. In order to realize a building that is in accordance with the specified functions and meets the technical requirements, safety, health, comfort, and convenience and sustainability of the surrounding environment, including knowing how much operational and maintenance costs are needed in the Trihamas Finance head office building and knowing how much operational and maintenance costs in the Trihamas Finance head office building. This study used primary and secondary data, standard operational maintenance procedures, building specifications, and maintenance budget allocation data. From calculations based on building revenues in 2022 and budgets for 2023 with a rate of return of 20 percent per year, it can be seen that the net present value is positive and the cost-benefit ratio is more than 1 then the project or investment is acceptable. Based on the results of the cost identification analysis incurred by the building manager in 2022, non-routine project maintenance/operational costs are in accordance with Trihamas Finance's building maintenance budget needs for roof floor repairs, as well as for ground floor and 8th floor tile repairs. In accordance with the Regulation of the Minister of Public Works Number: 24 / PRT / M / 2008 concerning Guidelines for Building Care and Maintenance, moderate damage costs are a maximum of 45 percent of the highest unit price of new building construction, for the same type / class and location